2016
DOI: 10.1007/s00417-016-3359-1
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and clinical characteristics of myopic posterior staphyloma in Caucasians

Abstract: This study confirms that the type I and II are the most common types of posterior staphyloma, as already highlighted in the literature. A significant association between the type of posterior staphyloma and the MRI ocular shape pattern, the OCT patterns of macular profile and the location of chorioretinal atrophy was highlighted. The correlation between the depth and the width of posterior staphyloma has demonstrated that the deeper the staphyloma, the wider it was. The deepest area of the posterior staphyloma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 20 publications
1
36
1
1
Order By: Relevance
“…A similar study was also conducted on Caucasian patients, combining A and B-scan US, 3D MRI, OCT, fundus autofluorescence (FAF), red free (RF) and color fundus photography, confirming that there is an association between the type of PS and MRI shape pattern of the eye, OCT macular profile pattern and chorioretinal atrophy. 23 In 2017, Shinohara et al used widefield OCT (WF OCT) combined to 3D-MRI to examine 100 eyes of 57 patients affected by PS. The authors found that WF OCT could provide high-resolution images, potentially replacing 3D-MRI in assessing PS.…”
Section: Posterior Staphilomamentioning
confidence: 99%
“…A similar study was also conducted on Caucasian patients, combining A and B-scan US, 3D MRI, OCT, fundus autofluorescence (FAF), red free (RF) and color fundus photography, confirming that there is an association between the type of PS and MRI shape pattern of the eye, OCT macular profile pattern and chorioretinal atrophy. 23 In 2017, Shinohara et al used widefield OCT (WF OCT) combined to 3D-MRI to examine 100 eyes of 57 patients affected by PS. The authors found that WF OCT could provide high-resolution images, potentially replacing 3D-MRI in assessing PS.…”
Section: Posterior Staphilomamentioning
confidence: 99%
“…In contrast, in high myopic eyes, MH formation is related to more complex pathogenetic mechanisms [ 33 38 ]. In addition to the anteroposterior traction caused by the strong adhesion of vitreous cortex and to the tangential traction from the tightening of the ILM, an important role is reserved to the abnormal growth of myopic eyes that may result in the development of posterior staphyloma (PS) defined as a progressive scleral ectasia of the posterior ocular globe wall ( Figure 1(a) ) [ 39 ].…”
Section: Pathogenesismentioning
confidence: 99%
“…[4] The prevalence of macular atrophy is higher in macular staphylomas compared to other types of staphylomas. [5]…”
Section: Introductionmentioning
confidence: 99%